(untitled) (Bangladesh Journal of Nuclear Medicine, 2023)
2-[18F]Fluoro-2-Deoxy-D-Glucose ([18F]FDG) is very effective and the most successful radiotracer for the assessment of glucose metabolism in the brain, heart, and lungs. It has also been used for imaging different tumors in oncology. The purpose of this study was to evaluate the stability and quality of [18F]FDG synthesized by the newly installed 18MeV Cyclotron facility at the National Institute of Nuclear Medicine and Allied Sciences (NINMAS). [18F]FDG was synthesized by nucleophilic fluorination of Mannose-triflate followed by basic hydrolysis with an IBA Synthera® auto synthesizer. [18F]FDG solution was collected in a sterilized vial after the filtration by a vented Millex®-GS 0.22µm syringe-driven hydrophilic filter. An aliquot of [18F]FDG solution was taken 0, 2, 4, 6, and 8 hours after the synthesis. All quality control parameters were measured in the first evaluated period, immediately (i.e., 0 hours) after synthesis. Radiochemical purity (RCP) was measured for all [18F]FDG samples and for all time points. The radiochemical and radionuclidic purity was more than 95% and 99.99% respectively. The [18F]FDG was physiochemically & microbiologically stable over 8 hours. Bangladesh J. Nuclear Med. 26(1): 44-50, 2023